(untitled) (Research, Society and Development, 2021)
In this article, we have the objective to present an educational proposal for Physical Geography that takes the resulting simulations of digital technologies as a means to offer to students next experiments to field work, done outside the school environment. The proposal is structured in three theories that are articulated with the objective of configuring a learning environment, namely: didactic sequences, hypothetical learning trajectories and pedagogical RPG. After presenting the theoretical concepts, the fictitious dialogues elaborated are analyzed, showing how the theories are articulated, elucidating the conduct of the teacher and the conduct of the student expected for the proposal.